Hubungan Antara Kemampuan Membaca Al-Qur’an Dengan Kemampuan Membaca Teks Bahasa Arab - Iwan, iin Junianti; Dalle, Ambo; Bachtiar, Fauziah (Universitas Negeri Makassar, 2024)
Abstract. This study is a correlational research using a quantitative approach that aims to determine the relationship between the ability to read the Qur'an and the ability to read Arabic texts of Grade VIII students of SMP IT Al-Huda Makassar. The independent variable in this study is the ability to read the Qur'an while the bound variable is the ability to read Arabic texts of students. The population in this study is all students in grade VIII of Al-Huda Makassar IT Junior High School which totals 37 students. Meanwhile, the sample in this study is grade VIII students of Al-Huda IT Junior High School Makassar which totals 37 students with a sampling technique, namely total sampling. The data from the research was obtained by providing a test to read the Qur'an and a test to read Arabic texts. The data analysis technique is descriptive and inferential analysis with the Pearson Product Moment correlation formula. The results of the study showed that the calculation of the relationship between the ability to read the Qur'an and the ability to read Arabic texts in grade VIII students of SMP IT Al-Huda Makassar had a correlation value (r_hitung) of (0.872) with a very strong interpretation. The value r_hitung is 0.872; and a value of r_tabel 0.325. So, r_hitung (0.872) > r_tabel (0.325) which means H_1 accepted and H_0 rejected. Thus, it can be concluded that there is a significant relationship between the ability to read the Qur'an and the ability to read Arabic texts in grade VIII students of SMP IT Al-Huda Makassar.Keywords: Correlation, Ability to read the Qur'an, Ability to read Arabic texts.